Investigation of the relationship between the diaphragm muscle relaxation therapy, voice emission and postural stability in amateur and professional singers of Academy of Music – preliminary study - Julia, Ciuryk; Dominika, Michalik; Katarzyna, Hordyjewicz; Paweł, Małecki; Grzegorz, Frankowski; Maciej, Kłaczyński; Małgorzata, Kulesa Mrowiecka (Journal of Measurements in Engineering, 2021)
The present study aims at presenting the impact of manual diaphragm relaxation therapy on the voice emission tested in an anechoic chamber and changes in the body posture during singing using the Zebris posturographic and pedobarographic platform. A pilot study on three cases has been conducted (patient 1 – male aged 21, student of the 2nd year of Academy of Music in Krakow, patient 2 – male aged 34, with more than 25 years of choral singing and advanced musical experience, patient 3 – female 24, with around 10 years of choral singing experience and primary musical school graduation). An original survey questionnaire was used, enabling determination the problematics associated with the profession of singer. A posturographic platform (Zebris) was used that revealed deviations during the scenic movement (by performing an appropriately developed repertoire). Subsequently, a voice emission examination was carried out in an anechoic chamber of the Department of Mechanics and Vibroacoustics, AGH University of Science and Technology. Directly after the examination, the examined individual was subject to a manual therapy lasting several minutes. The applied fascial techniques for diaphragm consisted in the implementation of a prolonged stretching of the myofascial complex with the use of low load. After the therapy, testing with the use of the aforementioned methods was repeated. The present study refers to the impact of the diaphragm function on voice emission parameters. In the pilot study for patient 1 and 2, 15 voice emission parameters improved. The analysis of the above results showed the variability before and after the diaphragm relaxation therapy in parameters such as Fo, Jitt and Shim. In the examined case of patient 1 and 2, the value of the parameter Jitt decreased by almost half, while Shim decreased by about 40 % after the therapy. However, such changes were not observed for patient 3. It may be influenced by many factors, such as stress or worse disposition on the day of the examination. The presented preliminary study expands the knowledge on the function of the diaphragm and the awareness of the function of ventilatory muscles during singing, which may result in enhanced efficiency of working with voice. In the future it is planned the study on bigger group students of Academy of Music in Krakow with the control group.